1958
DOI: 10.1063/1.1744410
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Photoconductivity in Cadmium Selenide Crystals

Abstract: Vacuum annealing of insulating and insensitive cadmium selenide crystals grown from the vapor phase increases their photosensitivity to a value at least as high as that of crystals sensitized by impurity incorporation. Such annealing-sensitized crystals have one hundred to one thousand times greater sensitivity than impurity-sensitized crystals at low light intensities and/or high operating temperatures. A new infrared quenching band with maximum at 1.0 ev is found at elevated temperatures, correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

1966
1966
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 15 publications
3
17
0
1
Order By: Relevance
“…When crystals of this same type are annealed above 500~ in vacuum, dark conductivity with an activation energy of 0.14 ev is found (17). This result indicates that the density of 0.14 ev donors is increased by the vacuum anealing to the point where the effects of oxygen adsorption can be overcome.…”
Section: Discussionmentioning
confidence: 84%
“…When crystals of this same type are annealed above 500~ in vacuum, dark conductivity with an activation energy of 0.14 ev is found (17). This result indicates that the density of 0.14 ev donors is increased by the vacuum anealing to the point where the effects of oxygen adsorption can be overcome.…”
Section: Discussionmentioning
confidence: 84%
“…Their values and the activation energies associated with the peaks determined by the initial rise method 22 are given in Table V. In the literature, TSC measurements have been reported on CdSe crystals using light. Bube et al 23 reported energy levels at 0.14, 0.3, 0.5, and 0.63 eV, Kindleysides et al 24 30°C (eV) 0.67 ± 0.03 10 -7 -10 -6 10 -8 -10 -7 1.1 ± 0.1 10 -6 -10 -5 10 -7 -10 -6 1.3 ± 0.01 10 -6 -10 -5 10 -7 -10 -6 -120°C (eV) 0.67 ± 0.03 10 -7 -10 -6 10 -8 -10 -7 1.3 ± 0.01 10 -7 -10 -6 10 -8 -10 -7 Table V, apart from that at 1.1 eV.…”
Section: Tscmentioning
confidence: 98%
“…Bube et al 23 postulated that levels at about 0.1 eV and 0.6 eV were different ionization states of an anion vacancy, while Yodogawa 19 stated that they were due to selenium vacancies. As discussed in the resistivity and photocurrent spectral response sections these levels could also be due to impurities substituting on the lattice sites.…”
Section: Tscmentioning
confidence: 98%
“…[1][2][3][4] However, little work was done on the influence of the ionizing radiations on their physical properties. A suitable band gap and optical properties recommend CdSe as a very promising material for optoelectronic applications like solar cell structures.…”
Section: Introductionmentioning
confidence: 99%